Cholinesterase activity as a potential biomarker for neurotoxicity induced by pesticides in vivo exposed Oreochromis niloticus (Nile tilapia) assessment tool for organophosphates and synthetic pyrethroids - Amin, Muhammad (Environmental technology, 2023)
Organophosphates (OPs) and synthetic pyrethroids (SPs) are the most popular broad spectrum pesticides, used in agriculture as they have a strong pesticidal activity while also being biodegradable in the environment. The present study aimed to demonstrate the effects of these pesticides on the Acetylcholinesterase (AChE) activity in brain, gills and body muscles of Oreochromis niloticus - an important enzyme for the assessment and biomonitoring pollution caused by neurotoxins in the environment. The fish were exposed for 24 and 48 h to the LC0 concentrations of the malathion (1.425 mg/L), the chlorpyrifos (0.125 mg/L) and the λ-cyhalothrin (0.0039 mg/L), respectively. The activity of the AChE was significantly increased (p < 0.05) at 24 h and decreased at 48 h (except for the chlorpyrifos-treated brain and gills while tissues had shown no activity at 48 h's exposure) in all pesticides-treated tissues. The maximum increase in the activity and inhibition in the AChE activity were recorded as +92% and -52% in the chlorpyrifos and the lambda-cyhalothrin exposed brain tissues, respectively. Thus, the alterations in the AChE activities indicated that the applied pesticides are highly neurotoxic to fish and the enzyme (AChE) could be used as a useful biomarker for estimation of water pollution